Certain Study of Bicomplex Matrices and a New Composition of Bicomplex Matrices (Global Journal of Science Frontier Research, 2018)
In this paper, we have studied Orthogonal and Unitary matrix in C 2 , some theorems and properties related to bicomplex matrix. We have defined the new concept over the bicomplex matrix, relation between bicomplex matrix and its complex component matrix, algebraic structure of bicomplex matrix in new system as well as the new definition of inverse of matrix in C 2 and some properties in new system. A similar relation between two bicomplex matrices is also defined in this paper.
Keywords: orthogonal bicomplex matrix; unitary bicomplex matrices; algebraic structure in new system; tranjugate matrix; inverse